Biomechanics of lower limb in badminton lunge: a systematic scoping review - Lam, W.; Wong, D. W.; Lee, W. C. (PeerJ, 2020)
Background: Badminton is a popular sport activity in both recreational and elite levels. A lot of biomechanical studies have investigated badminton lunge, since good lunge performance may increase the chances to win the game. This review summarized the current trends, research methods, and parameters-of-interest concerning lower-extremity biomechanics in badminton lunges.